Mode Choice Probability Between Bus and Railway Cianjur-Padalarang Route - Diah Eka Rahmawati; Eva Azhra Latifa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Travel between cities in the Bogor, Sukabumi, and Cianjur areas is only accommodated by road-based public transportation that is interstate bus. The government issued a policy to reactivate railroads from Bogor to Padalarang, so that the southern region of West Java are connected to the rail network. This research intention to analyze characteristics of socio-economic users, characteristics of trip users, and analyze how much passengers move from the current bus to the Cianjur-Padalarang train. Data were collected by distributing questionnaires using stated preference techniques and analyzed using binary logit difference model with linear regression. The attributes to be analyzed are the difference between travel costs, travel time, and frequency of departure. The characteristic of users were analyzed with descriptive statictic method. The socio-economic characteristics of the passengers obtained were majority is male, aged 21-30 years old, education level senior high school, worked as entrepreneurship, income Rp2.000.001-Rp3.000.000, transportation costs for a month Rp100.001-Rp300.000. The characteristics of trip users are dominated by origin from Cianjur destination to Padalarang to work (economy), the frequency of trips is 1-2 times per week, the reason choosing the bus because of the bus have more easier mobility, the main travel time is 121-150 minutes. The results of the calculation of model sensitivity, the potential for passenger transfer from bus to train will increase if the difference in cost and travel time between trains and buses is getting smaller, and the difference in frequency is getting bigger.